Design and Development of Video and Audio File Converter Applications - Sutrisno Situmorang; Jonas Franky Panggabean (Marqcha Institute, 2021)
A computer is a set of electronic devices or machines that work together based on the instructions given to them. Computers work systematically and as a tool for processing relatively large amounts of data with relatively high speed and accuracy. The design and manufacture of Video and Audio Converter Applications Using VB 6.0 is a very influential element in the launching of operational tasks in education and companies. Information that is not fast, precise, accurate, efficient, and effective can be solved by implementing this system. In compiling this final project, the author aims to simplify and speed up the learning process that is appropriate and accurate and saves time and space so that errors that hinder the smooth running of activities can be overcome.